Exhiber le crime vaincu : les fourches patibulaires et la justice criminelle sous l’Ancien Régime - Christophe Regina (Criminocorpus)
To study the gallows is to study primarily the story of power and its representations, the symbolic staging of the latter and physical anchoring in space and time. The gallows are involved in the affirmation of royal power since the monarchy undertook the reconquest of her authority to a greater extent under the Valois and Bourbon who have profoundly reorganized the administration of the kingdom and especially that of justice. This reorganization is manifested vividly in the reign of Louis XIV and points out that a redeployment of judicial prerogatives of nobility. The purpose of this article is to show the ways in which the use of gallows allows the monarch to assert his authority, not only by domesticating a nobility that not really fulfills its primary functions, to wage war, jealous of its privileges, but also by domesticating his subjects to be educated in order to preserve the public peace. It will also think in terms of performances: The gallows if they were deadly, they were provided feared?